The Improvement of Live Plaque Vaccine Production Technology - D. A. Sharov; A. A. Leshchenko; C. V. Bagin; S. V. Logvinov; A. V. Ezhov; A. G. Lazykin; D. A. Mokhov; V. V. Krupin; A. R. Ziganshin (Вестник войск РХБ защиты)
The article is dedicated to the possible improvement of the production technology of live plaque vaccines. The automated information system (AIS) of the control of the production of pharmaceuticals has been elaborated in the branch office of the «48 Central Scientific Research Institute» of the Ministry of Defence of Russia (Kirov) within the framework of the federal target program «The National System of Chemical and Biological Security of the Russian Federation». The AIS has been used for the improvement of the technology of submerged cultivation of live plaque vaccine. Strain EV, line NIIEG, as well as the upgraded fermenter BIOR-0,25 with the AIS of the control of the production have been used in this work. The problems of the improvement of the production technology of pharmaceuticals have been studied. The possibility of shared use of the fermenters and AIS of the control of the production of pharmaceuticals has been proven experimentally. This hardware system can accumulate, systemize and record scientific and technical information about all the operations. The above-mentioned studies allow to enhance the technological capabilities of the equipment and to improve the stage of the submerged cultivation in the production of live plaque vaccine.